Epidemiological and diagnostic study for some intestinal parasites that infect children in Diwaniya province - Hadi J. Al-Bayati, Mostafa; Alwahid Al-Hassany, Najim Abd- (Al-Qadisiyah Journal of Pure Science, 2017)
An Epidemiological study was conducted to determine the prevalence of intestinal parasites among outpatients and inpatients children in the hospitals and some private laboratories in the province of Diwaniya for the period from the beginning of November 2011 until the end of August 2012. The number of samples that have been collected (1057) stool samples, and the number of samples infected (223) sample After samples were examined in two methods, direct wet smear method using normal saline and iodine solution and staining method with modified acid-fast stain. The results showed that the overall incidence of intestinal parasites was approximately (21.1%), and males were more susceptible than females, where the percentage of males (21.4%) and females (20.8%), seven species were recorded belonging to the two parasitic groups, a parasitic protozo which included Entamoeba histolytica which scored highest infection rate, Giardia lamblia, and Cryptosporidium parvum parasites, which where (66.8%), (36.7%), and (17.9%) respectively. And a group of parasitic worms which included Hymenolepis nana, Enterobius vermicularis, Ascaris lumbricoides, and Taenia saginata parasites, infection rates were (2.7%), (1.8%), (1.8%) and (0, 4%), respectively. The results showed that July and August record the highest incidence of intestinal parasites from the rest of months, where the rates were (31.1%) and (28%) respectively, and the results also showed that the age groups (4-6) and (6-8) years were the two more infected with intestinal parasites. Afak and Hamzah eastern were the most infected, which where (30.8%) and (30.5%) respectively, and the infection mode with one parasite was more common than other modes of infections.